PERKAWINAN DI BAWAH UMUR DITINJAU DARI KACAMATA SOSIOLOGIS - Hermanto, Agus (Jurnal Mahkamah : Kajian Ilmu Hukum dan Hukum Islam, 2016)
"Marriage under age Judging from Glasses Sociology" The view of the Jurists' that the minimum age to marry is puberty signs of puberty there are two, namely bi al-alÃ¢maÃ¢t; for men marked by a dream or out of sperm, while women are marked with menstruation. bi al-sin; according to Hanafi, 18 year old male and a 17 year old woman. Maliki, is characterized by the growth of hair. Shafi, 15 years for men and 9 years for women. Hanbali, 15 years in both men and women. In Indonesia, the minimum limit married 19 for men and 16 for women. Age children who have reached adulthood, called puberty phase, at this age the child already has a full awareness of himself, sehingg he was given the burden of responsibility, especially religious and social responsibility.